2013
DOI: 10.1093/glycob/cwt094
|View full text |Cite
|
Sign up to set email alerts
|

Defining the structural origin of the substrate sequence independence of O-GlcNAcase using a combination of molecular docking and dynamics simulation

Abstract: Protein glycosylation with O-linked N-acetylglucosamine (O-GlcNAc) is a post-translational modification of serine/threonine residues in nucleocytoplasmic proteins. O-GlcNAc has been shown to play a role in many different cellular processes and O-GlcNAcylation is often found at sites that are also known to be phosphorylated. Unlike phosphorylation, O-GlcNAc levels are regulated by only two enzymes, O-GlcNAc transferase (OGT) and O-GlcNAc hydrolase (O-GlcNAcase or OGA). So far, no obvious consensus sequence has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Similar results were obtained from molecular docking and dynamics simulations analyzing models of various O -GlcNAcylated peptides in complex with Bacteroides thetaiotaomicron GH84 ( Bt OGA). These findings suggest that OGA substrate recognition generally lacks sequence sensitivity, though variations in sequence near the O -GlcNAcylation site are predicted to have some effect on OGA-glycopeptide binding affinity 47 . While structural features and adaptor proteins could also confer substrate specificity to OGA, evidence for these mechanisms is limited at this time.…”
Section: Substrate Recognition By Ogt and Ogamentioning
confidence: 96%
“…Similar results were obtained from molecular docking and dynamics simulations analyzing models of various O -GlcNAcylated peptides in complex with Bacteroides thetaiotaomicron GH84 ( Bt OGA). These findings suggest that OGA substrate recognition generally lacks sequence sensitivity, though variations in sequence near the O -GlcNAcylation site are predicted to have some effect on OGA-glycopeptide binding affinity 47 . While structural features and adaptor proteins could also confer substrate specificity to OGA, evidence for these mechanisms is limited at this time.…”
Section: Substrate Recognition By Ogt and Ogamentioning
confidence: 96%
“…It was also shown that OGA bounds to the peptide backbone through intramolecular hydrogen bonds and hydrophobic interactions . Molecular docking and dynamics simulations on models of Bt OGA in complex with O ‐GlcNAcylated peptides also gave similar results . From these observations, OGA substrate recognition was believed to lack sequence sensitivity, although differences in peptide sequences have led to small variations in predicting enzyme binding affinity …”
Section: Substrate Recognition By Ogamentioning
confidence: 80%
“…[43] Molecular docking and dynamics simulations on models of BtOGA in complex with O-GlcNAcylated peptides also gave similar results. [44] From these observations, OGA substrate recognition was believed to lack sequence sensitivity, although differences in peptide sequences have led to small variations in predicting enzyme binding affinity. [44] Recently, the partial structure of human OGA containing the catalytic and stalk domains revealed that OGA is present in a dimerized form creating a potential substrate-binding pocket (Figure 3).…”
Section: Substrate Recognition By Ogamentioning
confidence: 99%
See 1 more Smart Citation
“…A molecular view of the binding of short O -GlcNAc peptides in the active site of a catalytically impaired Cp OGA mutant, obtained through crystallographic studies, showed that interactions were limited to the sequence-independent stacking of the peptide backbone to a surface-exposed, conserved, aromatic residue in OGA ( 45 ). Conversely, a combination of molecular docking and molecular dynamics simulation suggests that although sequence-independent interactions with the peptide component do contribute, the affinity for OGA substrates varies as a function of the peptide sequence ( 46 ). It should be noted that peptide sequence and length may have entropic in addition to enthalpic effects on binding and that their precise conformations in the active site may affect not only binding but also turnover.…”
Section: Functional Insights From the O -Glcnacasementioning
confidence: 99%